The Influence of Federico García Lorca on Dai Wangshu’s Left-Wing Poetry Creation: The Theme of Death - Jiajing, Song (Sinología hispánica. China Studies Review, 2024)
Federico García Lorca was one of the representative poets of the Generation of ’27. His works demonstrate a strong opposition against the Spanish fascism. His contemporary poet Dai Wangshu got inspiration from his poems, which changed the direction of the Chinese poet’s creation. García Lorca’s comprehension of death led Dai to think over death, a theme he had never touched upon in his earlier poems. Dai got rid of his fear of death and started to express his understanding of death in his poems against the Fascist Japanese invaders at that time. Adopting an approach of the Aesthetic of Reception, the present article intends to analyze how García Lorca, his attitudes towards death and his way of putting it in his poems, made a deep left-wing influence on the Chinese poet.